SAFETY SYSTEM FOR LIQUEFIED PETROLEUM GAS (LPG) WITH MICROCONTOLLER BASED FUZZY DECISION TREE ALGORITHM - Yuda Irawan; Uci Rahmalisa; Refni Wahyuni; Hendry Fonda (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
The cause of the leak was caused by a hose that was no longer suitable for use in order to cause gas leakage that could have an effect on the LPG gas cylinder explosion. By making an alarm-and SMS-based LPG gas protection device with a MQ-6 sensor, users can see the leak in LPG gas. When this tool operates when a gas leak occurs, the MQ-6 has a leak in the LPG gas hose, so the alarm will sound. When active, the voice sends a command to Arduino to close the LPG gas valve. Then the alarm sends a command to the user via SMS to inform you that "gas leak has occurred" The implementation of this system is helpful so that users can easily see the gas leak so that they can take measures to combust on the gas stove. In this case, the desison tree algorithm will be used in which the internal node tester checks the attribute, each branch of the argument, and the study node class or class distribution leaf. After research, the results obtained are to generate a precision value of 90 per cent, a precision value of 100 per cent and an AUC value of 0.5 with a very good classification value (very good classification) on the PIR sensor and MQ-6. On the basis of these findings, it can be denied that the use of the yahoo sesison tree can be used in an acceptable and reliable manner.